Magneto‐Structural analysis of rotating electrical machines. Issue 1 (25th October 2016) - Haas, Stefan; Mair, Mathias; Ellermann, Katrin
Abstract: The vibrations of the stator core of a rotating electrical machine induce acoustic noise. These oscillations of the stator yoke are excited of the force density due to the magnetic field in the air gap. This requires a transient magnetic field analysis coupled with a dynamic mechanical analysis. Coupling these two different physical fields results in a high numerical effort and usually one direction of the interaction is disregarded. This paper presents a method to calculate the vibrations of a stator core under design operating conditions. For this purpose, harmonic electromagnetic excitation forces have been calculated in a linear magnetic field analyses using the finite element method. The resulting forces have been applied to a linear structural dynamic FE model in the frequency domain. The results of the calculations are harmonic velocities specified by amplitude and phase from the structural surface of the stator core. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)